Crizotinib: A Novel Strategy to Reverse Immunosuppression in Melanoma by Targeting Lactate Transport - Zhe Zhou; Xu Zhang; Susi Zhu; Waner Liu; Yeye Guo; Siyu Xiong; Cong Peng; Xiang Chen (MedComm)
ABSTRACT Lactate is a vital metabolite in cancer, significantly impacting tumor progression, metastasis, and overall survival. The CD147–monocarboxylate transporter 1 (MCT1) complex, a major lactate transporter, has emerged as a promising therapeutic target. However, no effective protein–protein interaction (PPI) inhibitors targeting the CD147–MCT1 complex have been identified. In this study, we found that the small‐molecule inhibitor crizotinib effectively disrupts the CD147–MCT1 interaction, leading to reduced lactate secretion from melanoma cells and decreased lactate uptake by macrophages. In vivo studies demonstrated that crizotinib treatment significantly suppressed tumor growth and enhanced responsiveness to immune checkpoint blockade therapy. Flow cytometry revealed that this metabolic intervention inhibits M2 polarization and reshapes the tumor immune microenvironment. Transcriptomic analysis further revealed that lactate induces C‐X‐C motif chemokine ligand 13 (CXCL13) expression in macrophages, which enhances melanoma invasiveness and impairs immune cell‐mediated cytotoxicity. Importantly, crizotinib suppresses CXCL13 expression by blocking lactate‐driven histone lactylation, thereby reversing the transcriptional reprogramming induced by lactate, as evidenced by reduced histone H3 lysine 18 lactylation (H3K18la) enrichment at the CXCL13 promoter. Taken together, these findings provide new insights into targeting metabolic‐immune crosstalk and highlight the value of disrupting CD147–MCT1 interactions to improve immunotherapeutic responses in patients with melanoma.